ANALYSIS OF FACTORS INFLUENCING THE INCOME OF FOOD STALL BUSINESS ENCINERS IN DENPASAR CITY - Eri Santi Muhimatul Ulya; Ni Luh Karmini (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Micro Business is one of the businesses that is growing rapidly and is a priority in national economic development efforts in Indonesia. Micro businesses have several advantages, including being able to overcome unemployment, namely being able to absorb labor, creating new job opportunities, opening up new jobs, and also as a business solution for small communities, being able to increase Gross Domestic Product (GDP) , and being able to survive during economic crises. . The culinary sector is one of the productive sectors that must be paid attention to by the Denpasar City government. Apart from the high demand for food and drink, culinary businesses are also easy to develop because they do not require a lot of capital to develop them. This research aims to analyze the influence of working capital, working hours, number of buyers, price, business location and marketplace utilization on the income of food stall micro businesses in Denpasar City. The population in this study were all micro-food stall businesses in the culinary sector in Denpasar City with a total sample of 93 obtained using a non-probability sampling method, namely purposive sampling. The data analysis technique used in this research is multiple linear regression analysis. The results of the analysis found that working capital, working hours, number of buyers, price, business location and marketplace utilization simultaneously and partially influence the income of food stall micro businesses in Denpasar City. Micro food stall business actors in Denpasar City who have strategic business locations earn more average income than those who are not strategic and business actors who use the marketplace earn an average of more income than those who do not use the digital marketplace.